Modeling Communication Semantics for Distributed Systems in Event-B - Dotti, Fernando Luís; Ribeiro, Leila (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2012: Anais do XIII Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2012.23083, 2012)
During the development of algorithms for distributed systems, one has to adopt clear assumptions about the semantics offered by the underlying communication platform in order to show that the algorithms under construction fulfill the expected liveness and safety properties. In this paper we propose a library of reusable formal specifications defining several classic communication semantics. The specification of each communication semantics is presented along with the proofs of the expected main properties of each model. The library was build using Event-B and properties were shown using the theorem proving approach with the Rodin system. While modeling a distributed application one can reuse models from the proposed library (by refinement or extension) without having to redo all the proofs related to the communication platform. Moreover, existing proofs can be used to show desired properties of the application.